Test the Effectiveness Volume of Hydroton Media on Mustard Plant (Brassica chinensis Var. Parachinensis) Using Auto Kapiler - Septia, Erfan Dani; Maftuchah; Nurfutika, Mifta (Journal of Tropical Crop Science and Technology, 2022)
This study aims to determine the level of effectiveness the hydroton growing media on mustard plants using the Auto Kapiler hydroponic method with 3 treatments; M1 with hydroton growing media of 2,54 liters (volume 50%), M2 with hydroton growing media of 3,78 liters (75% volume), and M3 with hydroton growing media of 5,04 liters (100% volume). The research was conducted on Jl. Tirtonadi RT. 25 / RW. 04, Jatikerto village, Kromengan sub-district, Malang district which will take place from April 25 to June 14, 2022. Some of the materials and tools used during the research are; hydroton growing media, auto capillary, AB-Mix nutrition, pH meter, and EC meter. Variable observations made consist of; plant height (cm), number of leaves (strands), leaf width (cm), root length (cm), and plant fresh weight (grams). Data analysis in this study used a simple Completely Randomized Design (CRD) with 4 replications and 3 treatments. The data obtained were further analyzed using the least significant Least Significant Different (LSD) α 5% level which was then further analyzed using a linear regression. The results showed that the M3 treatment (100% hydroton growing media volume was 5,04 liters) was better than the M2 treatment (75% hydroton growing media volume 3,78 liters) and M1 (50% hydroton growing media volume 2,52 liter).